Physical activity and persistent low back pain and pelvic pain post partum - Mogren Ingrid M (BMC, 2008)
Abstract Background The aims of this study were (i) to investigate the potential influence of pre-pregnancy regular leisure-time physical activity (PA) on the risk of persistent LBPP half a year after pregnancy, and (ii) to explore the starting time and prevalence of PA among women experiencing LBPP during pregnancy, in relation to remission or persistent LBPP half a year after pregnancy. Methods This study is a follow-up study of 639 women who reported LBPP during pregnancy. These women were sent a questionnaire at approximately six months after delivery. The respondents were divided into three groups: 'no pain', 'recurrent pain', and 'continuous pain'. Data were analysed using an independent samples t-test, Pearson's chi-squared test, and univariate and multivariate logistic regression analyses. Results 44.5% of subjects reported current PA at six months post partum. The mean starting time of PA was 2.6 months post partum and the mean number of current, weekly events of PA was 3.4; there were no differences between the groups. 82.2% reported previous PA at some period in life. Women with BMI ≥ 30 reported current PA to a lesser extent. The number of years of pre-pregnancy PA did not influence the risk of persistent LBPP. Conclusion Almost half of women who had experienced LBPP during pregnancy reported PA at six months post partum. The number of years of pre-pregnancy PA did not influence the risk of persistent LBPP. Obesity was a risk factor for not practising PA.